2002
DOI: 10.1103/physrevb.65.241408
|View full text |Cite
|
Sign up to set email alerts
|

Minimum energy paths for dislocation nucleation in strained epitaxial layers

Abstract: We study numerically the minimum energy path and energy barriers for dislocation nucleation in a twodimensional atomistic model of strained epitaxial layers on a substrate with lattice misfit. Stress relaxation processes from coherent to incoherent states for different transition paths are determined using saddle point search based on a combination of repulsive potential minimization and the Nudged Elastic Band method. The minimum energy barrier leading to a final state with a single misfit dislocation nucleat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 21 publications
(37 reference statements)
4
36
4
Order By: Relevance
“…Thus the experimentally observed critical thickness can be much larger than the equilibrium value depending on the kinetics of defect nucleation. Our preliminary results 23,24 showed a large variety of relaxation processes, including single dislocation nucleation, multiple dislocations, dislocations with different core structures, and dislocations nucleating on different depth in the film, which can be characterized by their different activation energies and energies of the final incoherent states. In this work, we focus on the nucleation and MEP leading to a final state containing only a single misfit dislocation with core located near the film-substrate interface.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus the experimentally observed critical thickness can be much larger than the equilibrium value depending on the kinetics of defect nucleation. Our preliminary results 23,24 showed a large variety of relaxation processes, including single dislocation nucleation, multiple dislocations, dislocations with different core structures, and dislocations nucleating on different depth in the film, which can be characterized by their different activation energies and energies of the final incoherent states. In this work, we focus on the nucleation and MEP leading to a final state containing only a single misfit dislocation with core located near the film-substrate interface.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous work 23 it was found that some features of dislocation nucleation are sensitive to the detailed form of the atomic potentials used. The results presented here are from systematic calculations for different values of cut-off distances for the 5 -8 potential (mϭ8, nϭ5).…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations